The potential of technology to meet world food needs in 2020 - Oram, Peter (International Food Policy Research Institute, 1995)
World population was about 2.5 billion in 1950; by 1988 it had doubled. Despite this unprecedented population explosion, global food supply kept pace with the additional demand for food. A technological revolution after World War II in the agriculture of the industrialized countries initially made this achievement possible. In the developing countries, where growth of food production had relied heavily on plowing up new land and on irrigation development, technology was increasingly responsible for production growth after 1965. Technology research in the following areas should receive high priority: (1) Improved application of technology to natural resource management; (2) Protection of crops from biotic stresses without heavy reliance on pesticides. (3) Genetic improvement of key crops. (4) Global action to advance scientific knowledge and its application.